2014
DOI: 10.1002/adfm.201400911
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Switching of Liquid Crystalline Order Permits Synthesis of Homogeneous Populations of Dipolar Patchy Microparticles

Abstract: The spontaneous positioning of colloids on the surfaces of micrometer-sized liquid crystalline droplets and their subsequent polymerization offers the basis of a general and facile method for the synthesis of patchy microparticles. The existence of multiple local energetic minima, however, can generate kinetic traps for colloids on the surfaces of the liquid crystal (LC) droplets and result in heterogeneous populations of patchy microparticles. To address this issue, here we demonstrate that adsorbate-driven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 62 publications
(90 reference statements)
5
33
0
Order By: Relevance
“…To address this issue, a recent study used reversible switching of the internal configurations of LC droplets to drive the colloids to a single location on the LC droplet surfaces. As shown in Figure 13 g , a transition triggered by adsorption of surfactants induces a long-range elastic force that sweeps adsorbed colloids to a unique location (the location of the single defect of the so-called preradial LC droplet configuration) (88). A subsequent reversal of this ordering transition results in a homogeneous population of bipolar LC droplets with colloids remaining at a single location (one of the boojum defects).…”
Section: Emulsions Of Liquid Crystalsmentioning
confidence: 99%
See 3 more Smart Citations
“…To address this issue, a recent study used reversible switching of the internal configurations of LC droplets to drive the colloids to a single location on the LC droplet surfaces. As shown in Figure 13 g , a transition triggered by adsorption of surfactants induces a long-range elastic force that sweeps adsorbed colloids to a unique location (the location of the single defect of the so-called preradial LC droplet configuration) (88). A subsequent reversal of this ordering transition results in a homogeneous population of bipolar LC droplets with colloids remaining at a single location (one of the boojum defects).…”
Section: Emulsions Of Liquid Crystalsmentioning
confidence: 99%
“…Because DNA can be assembled into a range of nanostructures based on sequence-specific interactions, and because the ordering of LCs is particularly sensitive to the presence of structure on these length scales, the use of DNA-programmed systems to trigger and regulate ordering in LC systems appears to be a particularly promising area of future research for the design of responsive materials.LC-templated synthesis of patchy particles. Recent studies have demonstrated that LC droplets can serve as templates for the synthesis of nonspherical and patchy particles (86, 88, 89). Whereas studies published so far address nonspherical particles templated from bipolar nematic droplets, other configurations of nematic droplets and droplets formed from other LC phases provide a very large parameter space of possible templates for particle synthesis.…”
Section: Concluding Remarks and Forward-looking Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that topological design of lattices, environments and boundaries can increase the stability and optimize the proficiency of materials or even create materials with novel properties, for example in topological insulators, 4,5 topological superconductors and superfluids 6 and liquid crystal colloids. [7][8][9][10] The topology of the material or material system -such as knottedness or entanglement -can profoundly influence both the static and dynamic properties of the system. 11,12 Examples of knotted molecular systems include knots of DNA rings, 13 knots of cyclic RNA molecules, 14 polymer knots 15 and templatesynthesized molecular knots.…”
Section: Introductionmentioning
confidence: 99%